Oophorectomy followed by postoperative chemotherapy for ovarian metastasis of colorectal cancer: a retrospective analysis - Zhao, Guangyue; Qiao, Yun; Ba, Yongchao; Song, Xing; Tian, Ye; Zhang, Yan; Guan, Ning; Hou, Xiaoqian; Zhang, Yuhua (Frontiers in Oncology, 2026)
BackgroundThe incidence of ovarian metastasis from colorectal cancer is low but the prognosis is extremely poor; however, the prognostic factors remain unclear and there are currently no guidelines for the treatment of ovarian metastasis from colorectal cancer. This study evaluated the impact of resection of ovarian metastasis from colorectal cancer and postoperative chemotherapy on patient prognosis.MethodsThis retrospective study analyzed patients with ovarian metastasis from colorectal cancer between January 2009 and December 2019. Factors with P < 0.1 in univariable analysis were considered as potentially prognostic factors and were incorporated into multivariable analysis with Cox proportional hazards regression models. Hazard ratios (HRs) with 95% confidence intervals (CIs) were analyzed. A two-sided P value < 0.05 was considered significant.ResultA total of 213 patients with ovarian metastasis from colorectal cancer were included in the study. Univariable analysis identified that the resection of primary tumor, extraovarian metastasis, oophorectomy, postoperative chemotherapy and mismatch repair (MMR) status as potentially prognostic factors. The median survival times in patients with and without oophorectomy were 25 and 11 months, respectively. Chemotherapy after surgery was associated with a longer median overall survival compared with patients without chemotherapy (25 versus 20 months). The median survival time for patients with dMMR status was 36 months, compared to 25 months for those with pMMR status. Multivariable analysis confirmed that oophorectomy (HR = 10.476, 95% CI, 5.536–19.825; P < 0.001), postoperative chemotherapy (HR = 2.232, 95% CI, 1.538–3.238; P < 0.001) and MMR status (HR = 1.967, 95% CI, 1.026-3.772; P = 0.042) were independent prognostic factors for overall survival in patients with ovarian metastasis from colorectal cancer.ConclusionOophorectomy, postoperative chemotherapy, and dMMR status may offer survival benefits for colorectal cancer patients with ovarian metastasis; however, the main findings from current study warrant further validations.